2011
DOI: 10.1016/j.ijimpeng.2011.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the kinematics of post-impact ice fragments

Abstract: Hail is more hazardous for aircraft engines compared to rain and snow, mainly, because of its solid nature and high water content. In extreme cases it can lead to engine flame out. In order to avoid such situations, aero engines should be designed to withstand hail ingestion. For this purpose we have studied the post-impact characteristics of ice, such as particle velocity and directions of travel. To achieve this goal, a large experimental program has been undertaken, in which spherical ice specimens were pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Studies by Guégan et al 5,6 and Pan and Render 7-13 on the impact of hail-size ice particles showed very high velocities for the first ejected fragments during impact. The velocity of those first ejected fragments was higher than the approaching ice particle velocity before impact.…”
Section: B Fragment Cloud Edge Velocitymentioning
confidence: 92%
See 2 more Smart Citations
“…Studies by Guégan et al 5,6 and Pan and Render 7-13 on the impact of hail-size ice particles showed very high velocities for the first ejected fragments during impact. The velocity of those first ejected fragments was higher than the approaching ice particle velocity before impact.…”
Section: B Fragment Cloud Edge Velocitymentioning
confidence: 92%
“…One of the important observations of Guégan et al and Pan and Render when studying impact of hailstones was the very shallow angle at which the particle fragments move in a direction perpendicular to the impact surface 5,6,17 . Angles of less than 2 o were observed.…”
Section: Additional General Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the inelastic regime the restitution coefficient decreased with increasing impact velocity and with increasing particle size. Guégan et al [47,48] • ) were tested for a range of velocities between 60 and 200 m/s. The experiments have shown that the post-impact particles are emitted in a circular cloud.…”
Section: Impact Physicsmentioning
confidence: 99%
“…Guégan et al 11 , performed ice impact visualization of 6 mm diameter frozen drops, while the tests described in this paper focus on the upper median diameter range of ice crystals encountered by engines operating under ice crystal environments (400 to 950 µm). Guégan studied the dynamics of the post-impact fragment cloud.…”
Section: Introductionmentioning
confidence: 99%